KUALITAS PELAYANAN PENGIRIMAN POS KILAT KHUSUS DI PT POS KEBONROJO SURABAYA - Nurlita Wulansari; Meirinawati Meirinawati (Universitas Negeri Surabaya, 2022)
Service is a form of public service. Currently the services that are often used are in the form of goods delivery services. Deposit service providers are activities carried out to receive, carry and or deliver certain types of postal letters, packages and money from the sender to the recipient at a fee. PT Pos Indonesia is one of the State-Owned Enterprises engaged in the delivery of goods / courier services. PT Pos Indonesia (Persero) offers various services for sending letters or documents, money, goods and packages. A complaint was found on the special express post delivery service with an estimate of only 2 days but until December 14, 2019 it had not yet arrived at the destination address. This study aims to determine the quality of the express mail delivery service of PT Pos Indonesia Kebonrojo Surabaya. The type of research in this research is descriptive with a qualitative approach. Data collection techniques in this research are through observation, interviews, documentation studies, literature studies which are processed and produce answers. Data analysis techniques carried out include data collection, data reduction, data presentation and drawing conclusions or verification. Based on the results of the research on the Quality of Special Express Post Delivery Services at PT Pos Indonesia Kebonrojo Surabaya seen from Kotler and Keller 2016 about five dimensions of service quality, namely physical evidence, reliability, responsiveness, assurance and empathy. Dimensions of physical evidence, the existing facilities in the room have been met. There are no excessive complaints about the facilities and comfort of the room provided. Dimensions of reliability, employees are able to provide and deliver the promised services in a timely and reliable manner. Delivery of goods made is in accordance with the SOP and delivered in accordance with the estimated time promised. Dimensions of responsiveness, employees are able to create good communication and the fast and responsive attitude given by employees makes consumers trust and be loyal to services. Dimensions of guarantee, consumers get a guarantee in accordance with the SOP. Consumers are guaranteed with insurance and employees do not lose consumers. Dimensions of empathy, consumers feel very helped by the services provided. The services provided are also in accordance with the expectations intended by consumers. The special express post delivery service at PT Pos Indonesia Kebonrojo Surabaya as a whole is in accordance with consumer expectations, as evidenced by prioritizing service quality and paying attention to the needs and complaints of consumers who have been loyal and trusted with special express post delivery services at the Kebonrojo Post Office Surabaya. Employees should use identification cards, pay attention to health protocols and provide queue numbers so that they are neat and in accordance with the order. Keywords:Quality of Service, Special Express Postal Delivery, Qualitative